2008
DOI: 10.1080/10887150801967134
|View full text |Cite
|
Sign up to set email alerts
|

Telework as a dependent care solution: Examining current practice to improve telework management strategies.

Abstract: To explore the influences of common telework practices on employee dependent care responsibilities, job performance, and work experience, quantitative and qualitative data were collected from 863 teleworking federal government employees with dependents. Respondents reported that teleworking positively influences their job performance and intentions to remain with their organizations. Teleworking assists them in meeting their dependent care responsibilities, but current policies and management practices undercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 22 publications
0
68
1
1
Order By: Relevance
“…Thus, support was found for the social exchange hypothesis, even after controlling for other antecedents of turnover. Furthermore, a decade-long study at the Institute for the Study of Distributed Work found that well-implemented telework programs can reduce employee turnover by 20% (Major et al, 2008), also supporting this theory. The hypothesis is then as follows:…”
Section: Social Exchange Theorymentioning
confidence: 87%
“…Thus, support was found for the social exchange hypothesis, even after controlling for other antecedents of turnover. Furthermore, a decade-long study at the Institute for the Study of Distributed Work found that well-implemented telework programs can reduce employee turnover by 20% (Major et al, 2008), also supporting this theory. The hypothesis is then as follows:…”
Section: Social Exchange Theorymentioning
confidence: 87%
“…A study that took place over a decade concluded that telecommuting reduced the cost of facilities by 35%, turnover by 20%, and training costs by 25% (Major et al, 2008). Another even found that it reduced corporate travelling costs (Andrew, 2004).…”
Section: Teleworkmentioning
confidence: 96%
“…Personnel evaluations in the public sector have shown improved employee morale/quality of worklife issues associated with telework (Joice, 2000). Government teleworkers report improved job performance because telework assists them in dependent care responsibilities (Major, Verive, and Joice, 2008). Mongioi, McNally, and Thompson (2010) believe telework arrangements improve emergency preparedness because they allow continuity of operations.…”
Section: Improved Productivitymentioning
confidence: 99%
“…However, the reward system should also accommodate exceptional individual performance that has a positive impact on the achievement of team goals. A majority of surveyed federal teleworkers believe telework eligibility approval processes could be more fair and consistent (Major, Verive, and Joice, 2008).…”
Section: Implement a Fair Reward Systemmentioning
confidence: 99%
See 1 more Smart Citation